The Regional Impersonal as a Mode of Dwelling: Structures of Embodiment in David Jones’s The Anathémata and Basil Bunting’s Briggflatts - Kotesovska, Lucie (Text Matters: A Journal of Literature, Theory and Culture, 2024)
The discussion of dwelling in this article focuses on T. S. Eliot’s controversial axiom of poetic impersonality as articulated in The Sacred Wood (1920) and practiced in The Waste Land (1922), and on how this axiom is rearticulated by his two younger contemporaries David Jones and Basil Bunting. I argue that in The Anathémata (1952) and Briggflatts (1966), their respective masterpieces, they reintegrate the ego absconditus through their distinct geo-aesthetical self-positioning which gives rise to “the regional impersonal” mode of poetic dwelling. This article explores the complex dialectics between the (neo)modernist claim of impersonality and the affective regional identification of the self-projecting consciousness in the two poems. While sharing Eliot’s regard for the poetic artifact, Jones and Bunting rehabilitate the notion of the poet’s cultural affiliation and representativeness as well as a culturally stimulated consciousness. Their act of self-sublimation is balanced by the material and sensual anchor of their regional allegiance. Further, the Eliotean fissure between the mind that experiences and suffers and the mind that creates resulting in a cascading multiplicity of voices in The Waste Land, is healed in Jones’s and Bunting’s poetic nostos and active mode of dwelling. Also, by giving resonance to numerous names and voices, mostly disembodied and obliterated entities, Jones’s and Bunting’s poetics introduces unifying strategies of impersonation reflecting their definite geo-cultural positioning. Eliot’s original aporia is thus not resolved but re-inhabited.